2009
DOI: 10.2741/3373
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-1 enhances migration of HEK293 cell by beta-catenin/E-cadherin degradation

Abstract: Migration is an important process during cellular activity and embryo development. We recently showed that Dickkopf-1(Dkk-1), an antagonist of Wnt/ beta-catenin signaling pathway, could promote trophoblast cell invasion during murine placentation. However, mechanism of Dkk-1 action on cell migration was not clear. The objective of this study was to further evaluate the effect of Dkk-1 on cell migration and to identify the underlining mechanisms. Functional assays with stable Dkk-1 transfected HEK293 cells reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Isoflavone genistein also inhibited the expression of Wnt-5a (130), suggesting that genistein can also modulate Wnt signaling. More recently, genistein was found to inhibit Dkk-1, an antagonist of the Wnt/␤-catenin signaling, by restoring membrane localization of E-cadherin and ␤-catenin in vitro (68). Finally, genistein has also been shown to be effective in the regulation of Hedgehog pathway (123).…”
Section: Natural Products and Human Healthmentioning
confidence: 95%
“…Isoflavone genistein also inhibited the expression of Wnt-5a (130), suggesting that genistein can also modulate Wnt signaling. More recently, genistein was found to inhibit Dkk-1, an antagonist of the Wnt/␤-catenin signaling, by restoring membrane localization of E-cadherin and ␤-catenin in vitro (68). Finally, genistein has also been shown to be effective in the regulation of Hedgehog pathway (123).…”
Section: Natural Products and Human Healthmentioning
confidence: 95%
“…A large number of experimental studies from our laboratory and others have shown that isoflavones, particularly genistein and daidzein, elicit anti-tumor effects by targeting NF-κB, Wnt, Notch-1, and Akt pathways in many cancers [207,415-420]. Due to its anti-tumor properties, isoflavones have been proposed as potential HIF-1 inhibitor.…”
Section: Natural Product-based Hif Inhibitorsmentioning
confidence: 99%
“…Sufficient data from in vitro and in vivo experimental studies have produced solid evidence supporting the role of genistein as a potent anti-tumor agent by targeting multiple signaling pathways such as NF-κB, Wnt, Notch-1, and Akt/mTOR in many different types of cancers [193199]. Accumulating evidence from multiple in vitro and in vivo studies has also indicated that genistein exerts an anti-oxidant activity by inhibition of ROS production, DNA oxidation, lipid peroxidation, and NF-κB-mediated inflammatory cytokines in various cells including cancer cells [200207].…”
Section: Genistein a Soy Isoflavone As A Potent Anti-oxidant Agenmentioning
confidence: 99%